2021
DOI: 10.1186/s12885-021-08554-5
|View full text |Cite
|
Sign up to set email alerts
|

Weight and waist-to-hip ratio change pattern during the first five years of survival: data from a longitudinal observational Chinese breast cancer cohort

Abstract: Background Body weight management was an important component in breast cancer survivorship care. The present study described the change patterns of body weight and waist-to-hip ratio (WHR) during the first 5 years of survival, and investigated potential factors associated with very substantial changes. Patients and methods Based on a longitudinal cohort with 1462 Chinese women with breast cancer, anthropometric measurements including body weight, h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…It is well recognized that Asian women have a lower body mass index (BMI) than Western women [ 31 ]. In addition, our previous study showed that less than 10% of Chinese women with breast cancer were obese, according to the BMI classification of the World Health Organization (WHO) [ 32 ]. Taken together, these data suggest that the beneficial impact of exercise on QoL may differ between Western and Chinese women.…”
Section: Introductionmentioning
confidence: 99%
“…It is well recognized that Asian women have a lower body mass index (BMI) than Western women [ 31 ]. In addition, our previous study showed that less than 10% of Chinese women with breast cancer were obese, according to the BMI classification of the World Health Organization (WHO) [ 32 ]. Taken together, these data suggest that the beneficial impact of exercise on QoL may differ between Western and Chinese women.…”
Section: Introductionmentioning
confidence: 99%
“…La hiperinsulinemia en mujeres obesas puede promover la carcinogénesis mamaria al aumentar la concentración del IGF y leptina. Estas interactúan en forma sinérgica con los estrógenos en las células epiteliales mamarias, promoviendo la angiogénesis (11).…”
Section: Obesidad Y Etiología Del Cáncer De Mamaunclassified
“…Chemotherapy also causes alternations in skeletal muscle and creates a predisposition to muscle atrophy and weakness ( 7 ). As a result, CVD burden associated with post-diagnosis weight gain has been observed to as long as 5 years in Asian patients ( 8 ). Of equal importance, excessive body fat in cancer survivors has been shown to affect quality of life and disease-free survival ( 9 ).…”
Section: Introductionmentioning
confidence: 99%